Passive, Wireless In Situ Millimeterwave Sensor with Mounted Dielectric Channels for Cure Monitoring of Carbon Fiber-Reinforced Polymers - Dorbath, Benedikt; Schür, Jan; Ziegmann, Gerhard; Vossiek, Martin (IEEE Sensors Journal, 2023)
Carbon fiber-reinforced polymer composites have become indispensable in certain industries, such as aeorspace, wind turbines, and automobiles, primarily due to their excellent mechanical robusteness combined with relatively low weight compared with materials of comparative strength. In addition to the choice of the matrix and fiber material within a composite, the curing process of the matrix material is essential for the final mechanical properties of the manufactured composite material. To monitor and optimize this critical curing process, we developed a passive, wireless in situ sensor that provides information about the momentary degree of cure by measuring the resonance frequency, which is dependent on the permittivity of the matrix material. This resonator-based sensor operates at around 45 GHz, which results in small geometric dimensions; its elliptical design with major axis diameters of 26 mm and 14 mm and a circuit board height of 475 μm aims to minimize the mechanical weakening of composites through the addition of the in situ sensors. Moreover, cylindrical dielectric channels mounted on top of the sensors’ orthogonally polarized patch antennas enable application of our sensor within conductive carbon fiber-reinforced polymers. The functionality of this sensor concept is confirmed with a precise simulation model and climate-controlled measurements during the curing process of epoxy resin and carbon fiber-reinforced polymers. Thereby, the measured change in resonance frequency and the predicted degree of cure of the carbon fiber-reinforced composite match closely, confirming the applicability of this sensor design in conductive carbon fiber-reinforced polymer composites.<br
Keywords: Sensors; Temperature measurement; Curing; Epoxy resins; Mechanical sensors; Permittivity measurement; Wireless sensor networks